2007
DOI: 10.1002/j.2050-0416.2007.tb00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Hardness Genes and Quality in Barley (Hordeum vulgare)

Abstract: Barley (Hordeum vulgare) genotypes were sequenced for polymorphism in the hardness genes, these being the three hordoindoline (hin a, hin b1 and hin b2) genes. The variation in haplotype was determined by sequencing for single nucleotide polymorphisms (SNPs). Polymorphism between each gene was then compared to grain hardness (three methods), malt quality characteristics (hot water extract and friability) and cattle feed quality. Two haplotypes were found in a set of forty barley genotypes. For hin a, two allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
2
16
0
1
Order By: Relevance
“…In this group of 81 spring barleys consisting of 73 USDA‐ARS National Small Grains Collection accessions selected for divergent DMD and eight modern cultivars, a large degree of sequence variation in Hina , Hinb‐1 , Hinb‐2 , and Gsp was observed (Table 1). The level of diversity is perhaps similar to that reported previously in less diverse data sets (Beecher et al, 2001; Caldwell et al, 2006; Fox et al, 2007). Beecher et al (2001) found three Hina and two Hinb alleles among eight North American barley cultivars and mapped Hinb to the short arm of chromosome 5H in a Steptoe × Morex mapping population.…”
Section: Discussionsupporting
confidence: 87%
“…In this group of 81 spring barleys consisting of 73 USDA‐ARS National Small Grains Collection accessions selected for divergent DMD and eight modern cultivars, a large degree of sequence variation in Hina , Hinb‐1 , Hinb‐2 , and Gsp was observed (Table 1). The level of diversity is perhaps similar to that reported previously in less diverse data sets (Beecher et al, 2001; Caldwell et al, 2006; Fox et al, 2007). Beecher et al (2001) found three Hina and two Hinb alleles among eight North American barley cultivars and mapped Hinb to the short arm of chromosome 5H in a Steptoe × Morex mapping population.…”
Section: Discussionsupporting
confidence: 87%
“…This FA model has been shown to perform well for these types of MET data [25][26][27][28][29] . This same statistical model was adopted for the feed grain traits.…”
Section: Malt Qualitymentioning
confidence: 91%
“…Recent studies have highlighted the benefits of using liner mixed models over traditional analysis of variance to calculate genetic and environmental effects for barley breeding data [25][26][27][28][29] . Using this mixed model analysis, we identified differences in genotypic responses across environments for the grain, malt and feed quality attributes measured in this study.…”
Section: Grain Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…It reflects a complicated correlation among the structural components of endosperm: starch, protein and b-glucan (Darlington et al, 2000). The quantitative trait locus (QTL), which is mainly responsible for the grain hardness trait, is found in the 7 th chromosome of the barley genome (Beecher et al, 2002), and is influenced by the genes hin a, hin b-1, and hin b-2 (Fox et al, 2007;Turuspekov et al, 2008). Grain hardness was observed to be relatively higher in barley genotypes with both high and low amylose content in grain (Jagtap et al, 1993).…”
Section: Traits Of Physical Grain Qualitymentioning
confidence: 99%